Acehnese's Digital Literacy Skills in Verification News from Social Media - Fizzy Andriani; Eni Kardi Wiyati; Dwi Ajeng Widarini; Muhammad Saifulloh (Ikatan Sarjana Komunikasi Indonesia, 2023)
Communication technology has recently become a new medium where society can choose information and the media they want to consume. The media can still influence their minds. Based on the National Survey of Internet User Penetration Data, in March 2019, by APJII (Internet Service Provider Association), the internet penetration rate in Aceh was recorded at 64.40% who accessed the internet. This research aims to find Acehnese's Digital Literacy Skills in Verification News from Social Media. The data collection method used for this study is a questionnaire instrument via Google Form to people in Nanggroe Aceh Darussalam (NAD) province. Meanwhile, secondary data was collected through literature studies and previous research. The result shows that the people of Aceh, especially millennials and Generation Z, have enough digital literacy skills to access digital media, understand content, and verify news.